Predictive factors for longer length of stay in an emergency department: a prospective multicentre study evaluating the impact of age, patient's clinical acuity and complexity, and care pathways. Issue 5 (28th February 2013) - Casalino, Enrique; Wargon, Mathias; Peroziello, Anne; Choquet, Christophe; Leroy, Christophe; Beaune, Sebastien; Pereira, Laurent; Bernard, Julien; Buzzi, Jean-Claude
Abstract : Background: It has been reported that emergency department length of stay (ED-LOS) for older patients is longer than average. Our objective was to determine the effect of age, patient's clinical acuity and complexity, and care pathways on ED-LOS and ED plus observation unit (EDOU) LOS (EDOU-LOS). Methods: This was a prospective, multicentre, observational study including all patients attending in 2011. Age groups were: I, <50; II, ≥50–64; III, ≥65–74; IV, ≥75–84; V, ≥85 years. Univariate and multivariate analyses were performed. Results: Of 125 478 attendances, 20 845(16.6%) were of patients aged ≥65 years. Multivariate analysis found significant predictors for ED-LOS (C-statistics 0.79, p<0.0000001) to be: arrival mode (ambulance, OR 1.13 (95% CI 1.08 to 1.18)); acuity level (level 4, OR 1.24 (95% CI 1.21 to 1.28); level 1–3, OR 1.54 (95% CI 1.5 to 1.59)); haematological examinations (OR 3.34 (95% CI 3.15 to 3.56)); intravenous treatment (OR 1.58 (95% CI 1.47 to 1.69)); monitoring of vital signs (OR 1.89 (95% CI 1.69 to 2.10)); x-ray examinations (OR 1.53 (95% CI 1.45 to 1.61)); CT/MRI/ultrasound (OR 2.60 (95% CI 2.39 to 2.82)); and specialist advice (OR 1.39 (95% CI 1.30 to 1.48)). For EDOU-LOS (C-statistics 0.81, p<0.0000001) we found: age group (II, OR 1.19 (95% CI 1.16 to 1.22); III, OR 1.42 (95% CI 1.38 to 1.46); IV, OR 1.69 (95% CI 1.65 to 1.74); V, 2.01 (95% CI 1.96 to 2.07)); acuity level (level 4, OR 1.31 (95% CI 1.27 to 1.35); level 1–3, OR 1.71 (95% CI 1.66 to 1.77)); haematological examinations (OR 7.81 (95% CI 7.23 to 8.43)); intravenous treatment (OR 1.95 (95% CI 1.8 to 2.12)); x-ray examinations (OR 1.95 (95% CI 1.85 to 2.06)); CT/MRI/ultrasound (OR 6.74 (95% CI 5.98 to 7.6)); specialist advice (OR 2.24 (95% CI 2.07 to 2.42)); admission to a medical or surgical ward (OR 0.61 (95% CI 0.54 to 0.68)); and transfer (OR 1.79 (95% CI 1.54 to 2.07)). Conclusions: Whereas ED-LOS and EDOU-LOS seem to be directly related to patients' acuity and complexity, notably the need for diagnostic and therapeutic interventions, only EDOU-LOS was significantly associated with age and proposed care pathways. We propose that EDOU-LOS measurement should be made in EDs with an OU.